2021
DOI: 10.1002/ejp.1777
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of an educational movie to improve pain and dysfunctional behavior in school children: A randomized controlled trial

Abstract: Background: Chronic pain in children is a serious issue, therefore calling for effective prevention/intervention measures. This study aimed to evaluate the efficacy of an educational movie on pain knowledge in school children in general and on pain-related behaviours and pain intensity in those who are affected by chronic pain.Regarding those affected, the association between pain knowledge and intensity, as well as the potential mediating effect of pain-related behaviours, were investigated. Methods: Recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…On the true preventative side, very recently, pain education is being delivered to and studied in a one-on-one format in healthy children [36,37] as well as in larger groups at middle schools [31,[38][39][40][41][42][43]. Rheel et al [36] found that healthy children (aged 8-15 years) who watched a 15minute pain education video before an experimental heat pain task had higher pain knowledge and higher heat pain thresholds after watching the video compared to a group of children who did not watch this video.…”
Section: Pain Education As a Preventive Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…On the true preventative side, very recently, pain education is being delivered to and studied in a one-on-one format in healthy children [36,37] as well as in larger groups at middle schools [31,[38][39][40][41][42][43]. Rheel et al [36] found that healthy children (aged 8-15 years) who watched a 15minute pain education video before an experimental heat pain task had higher pain knowledge and higher heat pain thresholds after watching the video compared to a group of children who did not watch this video.…”
Section: Pain Education As a Preventive Strategymentioning
confidence: 99%
“…No pre-post differences however, were found regarding parental pain catastrophizing or parental pain vigilance and awareness. Studies examining whether delivering pain education to larger groups of children (age range: 10-15 years) in a school/classroom setting (i.e., group sizes ranging from 15 to 70 students) via a lecture and/or a video demonstrate beneficial changes in pain knowledge, healthier beliefs regarding pain [32,[39][40][41][42][43][44], and ultimately positive behavioral outcomes such as less pain medication use [41]. Positive behavioral results were larger when the initial pain education session was supplemented by short video booster sessions after a few months [41].…”
Section: Pain Education As a Preventive Strategymentioning
confidence: 99%
“…PSE comprises one or more patient-tailored educational sessions, typically face-to-face between a therapist and patient, and supported by educational materials. Evidence in children and adolescents in clinical 43,44 and nonclinical [45][46][47][48] settings shows that PSE results in increased pain knowledge, 43,[45][46][47][48][55][56][57] more functional pain beliefs, 46,56,57 less catastrophic worry about pain, 58 less pain-related fear, 44 less functional disability, 44 less medication use, 45 higher pain thresholds, 44,48 higher school attendance, 45 and decreased fear of physical activity. 56 There is less evidence that PSE for both adults and children results in reduced pain intensity, 43,44,59 pressure pain thresholds, 60,61 or anxiety.…”
Section: Pain Science Education As Part Of Comprehensive Pain Carementioning
confidence: 99%
“…Lea Höfel, Anja Schramm, Bianca Roth, Mathias Georgi und Johannes-Peter Haas Altersgerechte Informationsvermittlung Eine ansprechende Gestaltung und Didaktik in schriftlicher, auditiver oder visueller Form kann zum Wissenserwerb beitragen [5]. Beispiele hierfür sind die YouTube-Videos "Wissenswertes zum Schmerz" des ‚Zentrums für Schmerztherapie junger Menschen' oder "Den Schmerz verstehenund was zu tun ist in 10 Minuten!"…”
Section: Schmerz-know-how Für Kids Und Teenagerunclassified